USE OF INTERNET RESOURCES FOR DISTANCE LEARNING OF A FOREIGN LANGUAGE - Aksenov Ilia Antonovich; Neverova Natalia Viktorovna; Rybakova Ludmila Victorovna; Sharoiko Ekaterina Aleksandrovna; Syutkina Marina Yuryevna; Linok Larisa Vladimirovna; Emelianova Elena Pavlovna; Panfilov Stepan Alexandrovich; Kabanov Oleg Vladimirovich; Khrameshin Sergey Nikolaevich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Various training systems that have been quite effective in the past do not completely correspond to the current realities. Today they do not take into account modern human capabilities, as well as the needs of production. Over the past decades, the process of computerization has been widely used in literally all spheres of human activity. In conditions of intensification of various processes, it is difficult to imagine a modern educational organization without its own website, internal corporate network, and constant access to the Internet. The Internet system in the best way favors the study of a foreign language remotely, since with the help of social networks and all kinds of chats, we can communicate with native speakers at any time of the day, thereby practicing not only spoken language, but also grammar.